Sociomaterial entanglement in one-to-one computing classrooms: exploring patterns of relations in teaching practices. Issue 4 (2nd October 2021) - Meyer, Bente; Bergström, Peter; Wiklund-Engblom, Annika
ABSTRACT: Although many studies have investigated teaching in one-to-one computing classrooms, not many have considered the material dimension as equally important to the human dimension. Thus, by using a sociomaterial perspective, we aim to broaden the discussion about emergent teaching practices in Nordic classrooms where students use tablets as personal devices. We therefore provide three vignettes from ethnographic classroom studies in Sweden, Finland and Denmark. These illustrate how tablets were used in specific classrooms. In our qualitative analysis of the vignettes, we draw on the concept of patterns of relations to describe the dynamic entanglements of the emergent teaching and learning practices. These are patterns of 1) interrogation, 2) spacemaking and 3) materialisation. Our findings show that tablets do not enter empty learning spaces but are woven into and participate in forming ways of teaching in one-to-one classrooms. Teachers must therefore learn to engage with and manage complex relationships rather than learn how to use an iPad.